Executive's guide to COSO internal controls : understanding and implementing the new framework - Moeller, Robert R. (Hoboken : John Wiley, 2013)
Essential guidance on the revised COSO internal controls framework Need the latest on the new, revised COSO internal controls framework? Executive's Guide to COSO Internal Controls provides a step-by-step plan for installing and implementing effective internal controls with an emphasis on building improved IT as well as other internal controls and integrating better risk management processes. The COSO internal controls framework forms the basis for establishing Sarbanes-Oxley compliance and internal controls specialist Robert Moeller looks at topics including the importance of effective system.
CHAPTER FIVE COSO Internal Control Components: Risk AssessmentRISK ASSESSMENT COMPONENT PRINCIPLES; RISK IDENTIFICATION AND ANALYSIS; RISK RESPONSE STRATEGIES; FRAUD RISK ANALYSIS; COSO RISK ASSESSMENT AND THE REVISED INTERNAL CONTROL FRAMEWORK; NOTES; CHAPTER SIX COSO Internal Control Components: Control Activities; COSO CONTROL ACTIVITY PRINCIPLES; Control Activity Principles: Integration with Risk Assessment; Enterprise-Specific Control Activity Factors; Business Process Control Activities; Types of Transaction Control Activities.
Keywords: Organizational effectiveness; Auditing, Internal; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Auditing, Internal; Organizational effectiveness; Electronic books